OPTIMALISASI PENGGUNAAN DANA DESA DALAM MEWUJUDKAN KESEJAHTERAAN MASYARAKAT DESA GENENG BATEALIT JEPARA - Dwi Bambang Hermawan; Aris Suliyono (Cattleya Darmaya Fortuna, 2026)
This research aims to analyze the optimization of the use of Village Funds in realizing the welfare of the people of Geneng Village, Batealit District, Jepara Regency. The research method used is descriptive qualitative with data collection through interviews, observation and documentation. The research results show that the quality of village officials' human resources is the main factor in determining the effectiveness of determining the Village Fund priority scale. Competent village officials are able to formulate development programs according to the real needs of the community, increase citizen participation, and ensure transparency and accountability in the use of Village Funds. However, obstacles such as limited apparatus capacity, lack of continuous training, and limited supporting facilities still influence the optimization of Village Fund management. This research recommends increasing the capacity of village officials, strengthening infrastructure, and developing community participation mechanisms so that the Village Fund can more effectively promote community welfare in a sustainable manner.